Defects in polynucleotide phosphorylase impairs virulence in Escherichia coli O157:H7 - Hu, Jia; Zhu, Mei-Jun (Frontiers in Microbiology, 2015)
Polynucleotide phosphorylase (PNPase) is reported to regulate virulence in Salmonella, Yersinia spp. and Campylobacter jejuni, yet its role in Escherichia coli O157:H7 has not been investigated. To gain insights into its roles in E. coli O157:H7 virulence, pnp deletion mutants were generated and the major virulence factors were compared to their parental wild type strains. Deletion of pnp in E. coli O157:H7 dramatically decreased stx2 mRNA expression and Stx2 protein production, and impaired lambdoid prophage activation in E. coli O157:H7. Quantitative PCR further confirmed that the Stx2 phage lytic growth was repressed by pnp deletion. Consistent with reduced Stx2 production and Stx2 phage activation, the transcriptional levels of genes involved in phage lysis and replication were down-regulated. In addition, disruption of pnp in E. coli O157:H7 decreased its adhesion to intestinal epithelial cells as well as cattle colonic explant tissues. On the other hand, PNPase inactivation in E. coli O157:H7 enhanced Tir protein content and the transcription of type three secretion system components, including genes encoding intimin, Tir and EspB as well as LEE positive regulator, Ler. Collectively, data indicate that PNPase has pleiotropic effects on the virulence of E. coli O157:H7.